Accuracy and bias in first impressions of attachment style from faces. Issue 5 (24th January 2020) - Alaei, Ravin; Lévêque, Germain; MacDonald, Geoff; Rule, Nicholas O.
Abstract: Objective: People gather important social information from subtle nonverbal cues. Given that one's attachment style can meaningfully affect the quality of one's relationships, we investigated whether people could perceive men's and women's attachment styles from photos of their neutral faces. Method: In two studies, we measured targets' attachment styles then asked participants (total N  = 893) to judge the male and female targets' attachment anxiety and avoidance from photos of their neutral faces (total N  = 331) and to report their own attachment anxiety and avoidance. Results: Participants detected men's attachment style from face photos significantly better than chance in an initial exploratory study and in a preregistered replication but did not consistently detect women's attachment style from their face photos. Moreover, participants' own attachment style biased these first impressions: Individuals with greater attachment anxiety viewed others as more anxiously attached. Conclusions: People can detect some hints of unacquainted others' attachment styles from their faces but their own anxious attachment can bias these judgments.